Dementia and social work practice : research and interventions - Cox, Carole B. (Springer Pub., 2007)
Dementia is one of the most devastating illnesses as it involves a progressive decline in mental functioning leading to eventual total incapacity, affecting all aspects of diagnosed individuals. This book talks about the many factors associated with dementia and its care, and the ways in which social work involvement can be most valuable.